43.3k views
5 votes
2x + 5y = -3
2x + 2y = 6

2 Answers

3 votes

Answer:

(6, - 3 )

Explanation:

Given the 2 equations

2x + 5y = - 3 → (1)

2x + 2y = 6 → (2)

Subtracting (1) from (2) term by term will eliminate the x- term

(2x - 2x) + (2y - 5y) = 6 - (- 3), that is

- 3y = 9 ( divide both sides by - 3 )

y = - 3

Substitute y = - 3 in either of the 2 equations and solve for x

Substituting y = - 3 in (1)

2x + 5(- 3) = - 3

2x - 15 = - 3 ( add 15 to both sides )

2x = 12 ( divide both sides by 2 )

x = 6

Solution is (6, - 3 )

User ClassicThunder
by
4.6k points
5 votes

Answer: x = 6 and y = -3

Step-by-step explanation: What we have in this question is a pair of simultaneous equations,

2x + 5y = -3 ———(1)

2x + 2y = 6 ———(2)

We shall use the elimination method to solve this since none of the variables has a coefficient of 1. We multiply equation (1) by 2 and multiply equation (2) by 5 {to eliminate the y variable). So we now have,

2x + 5y = -3 ——— x2

2x + 2y = 6 ——— x5

4x + 10y = -6 ———(3)

10x + 10y = 30 ——(4)

Subtract equation (3) from equation (4)

10x - 4x +(10y - 10y) = 30 - (-6)

6x = 30 + 6

6x = 36

Divide both sides of the equation by 6

x = 6

Having calculated that x = 6, substitute for the value of x into equation (1)

2x + 5y = -3

2(6) + 5y = -3

12 + 5y = -3

Subtract 12 from both sides of the equation

5y = -3 - 12

5y = -15

Divide both sides of the equation by 5

y = -3

Therefore x equals 6 and y equals -3

User Joey Gibson
by
5.0k points